Os anais de encontros científicos como fonte de informação - Lina Laura Crivellari Cardoso de Mello (2001)
We analyzed the characteristic of scientific meetings proceedings as an information source by studying the four national events annals, which is periodically carried out in the areas of Library Science and Veterinary Medicine. In the annals as publication in all we analyzed the editorial responsibility and form of disclosure and physical presentation. In the published work was found: 1) number and types of publications, 2) form (abstract or full content) of publication, 3) qualified institutional affiliation of autotores, 4) publication of languages, 5) Bibliographic standardization, 6) processes selection and critical judgment and 7) frequency with which they are published through other means. Data were collected through a questionnaire with authors, interviews with organizers of events and examination of the proceedings themselves. It concludes that the characteristic of the proceedings varies according to the aria and your profile can contribute to the proper treatment of information services as well as for improving the editorial quality.